Souvenirs sur Marx et Engels. - Engels, Friedrich; Lenin, Vladimir Iljitsj; Lafargue, Paul; Liebknecht, Karl; Bebel, August (Moscou : Editions du Progrès, 1982)
Bibliotheek François Vercammen
Frans
Monografie